Severe systemic lupus erythematosus induced by isoniazide - Rakotoson, J L; Randriamanana, D; Rakotomizao, J R; Andrianasolo, R; Rakotoarivelo, R; Andrianarisoa, A C F (Revue de pneumologie clinique, 2009)
The authors report a rare case of low register systemic lupus erythematosus with renal attack and neurological armature by isoniazid. The patient was a 23-year-old woman presenting a lupus induced by isoniazid 1 month after the treatment of pleural tuberculosis. Antinuclear antibodies, anti-native DNA, anti-ENA, anti-Sm, anti-SSa, anti-SSb and antihistone were present. The symptoms included arthralgia, fever, anaemia, pleural effusion, pericarditis and anasarca. She presented a renal and neurological attack, accounting for the gravity of the disease. The treatment consisted of the interruption of the isoniazid and a bolus of methyl-prednisolone during 3 days relayed by an oral corticosteroid. The evolution was favourable after 8 months of corticosteroids.